Productivity, misallocation, and special tax regimes in the Dominican Republic - Rodrigo Azuero; Mariano Bosch Mossi; Marvin Cardoza; Dennis Sanchez (Inter-American Development Bank (IDB), 2019)
This paper advances understanding of the relationship between tax policy and productivity, taking advantage of unique data from the Dominican Republic to document a significant negative impact of tax regulations on total factor productivity (TFP). It begins by estimating productivity using administrative records provided by the tax authorities. Then, it estimates the extent to which misallocation of resources might be limiting TFP using the Hsieh and Klenow (HK) methodology. Finally, it analyzes the tax regulation and provides suggestive evidence about how some provisions might be contributing to the misallocation of resources observed in the Dominican Republic. The paper finds that if misallocation of resources is eliminated from the economy, TFP will increase by a factor of 3.5. Several regulations generate discontinuities in the average rate of taxation, and tax reductions designed for small businesses are actually used by large and unproductive firms, which may be contributing to the overall misallocation observed in the Dominican Republic.
Keywords: H26; H30; J8; L11; L51; 330; firm size; general fiscal policies; labor regulation; productivity; tax evasion and avoidance